Evaluation in health-related quality of life indicators for chronic kidney disease using fuzzy numbers - Noor Jamalina Mohd Jamal (Terengganu: Universiti Malaysia Terengganu, 2014)
Health-related quality of life (HRQoL) is the subjective perception of either the effect of a disease or its treatment on one's health and overall quality of life. HRQoL measurements express important information about the patients. HRQoL can be assess through several valid and reliable questionnaires. Patients' perceptions of the impact of disease and treatment on the indicators such as physical, psychological, social function and well being are normally investigated.